The use of English loanwords in Malay: perceptions of students from a language faculty - Alias, Aliah Eilina (Kulliyyah of Languages and Management (KLM), 2021)
The increasing western culture and economic influence all over the world after the World War Two (Jones, 2007) has seen the growing use of English language as a second language in Malaysia. Despite some resentment towards the language as a colonizer’s language (Stephen, 2013), the influence of the English language can be seen in the Malay language in the use of English loanwords. Using the qualitative research design, this study investigated the language students’ perceptions of the use of English loanwords in the Malay Language. The research questions are: 1. What are the factors that influence the language students’ choice of English loanwords?; 2. What are their opinions about the use of English loanwords among Malaysians in general? Six language students from Kulliyyah of Languages and Management, International Islamic University Malaysia were interviewed online via the Google Meet platform. The data were analysed using the thematic analysis by Braun and Clarke (2006). The findings revealed that the factors that influenced the students to use English loanwords are familiarity, filling lexical gaps and the media influence. They also had mixed opinions on this phenomenon. While they were able to recognize the importance of English loanwords in communication, they were also concerned that it can compromise the authenticity of the Malay Language. This shows that despite the benefits of borrowing words from other languages, the native language is perceived as more than just a means of communication; it represents culture and identity. There were also suggestions that the Dewan Bahasa dan Pustaka (DBP) should control the number of English words being borrowed and adopted into the language.